(untitled) (Research, Society and Development, 2022)
The hyposodium diet is characterized by low sodium content, which contributes to it having low sensory appeal and ends up reflecting on the acceptability of meals. Herbal salt, consisting of aromatic herbs is an alternative to refined salt, and can be used in diets with low sodium content in order to provide greater palatability, besides being an excellent source of nutritional compounds. Therefore, the objective of this work is to identify the acceptability of the insertion of herbal salt as a substitute for refined salt in the seasoning of hyposodic diets in a public hospital in the city of São Paulo. It is an experience report of an interinstitutional action carried out by nutrition trainees, under the guidance and supervision of teachers and nutrition team of the Hospital Unit, which authorized and enabled the development of the action. This experience had the voluntary participation of 38 subjects of both sexes, aged between 27 and 89 years, who reported improvement in the taste of meals with the addition of herbal salt, both among women (75%), and among men (61.11%), totaling 26 (68.42%) positive responses. From the results of this study it was observed that herbal salt allowed patients an improvement in the enhancement of the flavor and palatability of meals, contributing to the greater acceptance of the hyposodic diet, and can even be implemented as an alternative to refined salt served in normossodic diets served in this Unit.